2009
DOI: 10.1111/igc.0b013e3181b76640
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve of Laparoscopic Radical Hysterectomy With Pelvic and/or Para-Aortic Lymphadenectomy in the Early and Locally Advanced Cervical Cancer

Abstract: Laparoscopic radical hysterectomy is a feasible and safe treatment modality in early and even locally advanced cervical cancer without decreasing survival. Surgical outcome was improved with experience, and the complication rate related to operation of group 1 was higher than that of group 2. There was no significant difference in survival between the 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 23 publications
5
66
3
1
Order By: Relevance
“…In this regard were grouped top 50 and next 50 hysterectomies. Authors concluded that all of the aforementioned parameters were improved in group 2 [17]. Similar results were published by Hwang et al for uterine cervical cancer in the early stages who received laparoscopic radical hysterectomy with lymphadenectomy.…”
Section: Laparoscopic and Robotic Learning Curve Technique In Gynecolsupporting
confidence: 75%
“…In this regard were grouped top 50 and next 50 hysterectomies. Authors concluded that all of the aforementioned parameters were improved in group 2 [17]. Similar results were published by Hwang et al for uterine cervical cancer in the early stages who received laparoscopic radical hysterectomy with lymphadenectomy.…”
Section: Laparoscopic and Robotic Learning Curve Technique In Gynecolsupporting
confidence: 75%
“…In addition, the movement of the robotic arm results in stable traction and counter traction and excellent 3-dimensional view within a narrow space. 19,22 A recent meta-analysis revealed that the blood loss in the RRH group can be as low as 78 or 82 mL. 16,35,36 In our study, the mean blood loss was much higher compared with those studies but was still significantly lower in the RRH group versus the TLRH group.…”
Section: International Journal Of Gynecologicalcontrasting
confidence: 51%
“…In open surgery, as the difficulties of operations increase, the probability of ureteral injury increases by 0-2.0% (Uccella et al, 2007;Chong et al, 2009), whereas the probability of ureteral injury in laparoscopic operations increases by 0.2-6.0% (Cholkeri-Singh et al, 2007;Tanaka et al, 2008). This increased risk is due to the limitations of visual exposure, the lack of touch, and the use of an energy apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…As laparoscopic hysterectomy and retroperitoneal operations, such as pelvic lymph node dissections, have increasingly been adopted, the occurrence rate of laparoscopic ureteral injury has also increased (Cholkeri-Singh et al, 2007;Tanaka et al, 2008). Furthermore, the rate of ureteral injuries resulting from laparoscopic operations is substantially higher than that resulting from celiotomies (Uccella et al, 2007;Chong et al, 2009). Ureteral injury results in not only increased medical expenses, but also increased physical and emotional damage for patients.…”
Section: Introductionmentioning
confidence: 99%